An Investigation of the Strength Properties of Fly Ash and Metakaolin-Based Geopolymer Mortars Containing Multi-Wall Carbon Nanotube, Nano Silica, and Nano Zinc - Seloğlu, Maksut; Tanyıldızı, Harun; Öncü, Mehmet Emin (My University, 2023)
In this study, the mechanical properties of geopolymer mortar composites containing different nanomaterials were investigated. Metakaolin (MK) and fly ash (FA) were used as binders in geopolymer mortar samples. Sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) solution (12 M) were used as alkali activators. Multi-walled carbon nanotube (MW-CNT), nano-SiO2 (NS), and nano-ZnO (NZ) were used in the study. Geopolymer mortar samples without nanomaterials were determined as control samples, and geopolymer mortar samples containing 0.5% by weight of MW-CNT, NS, and NZ were prepared. All prepared samples were cured at 20±2 °C laboratory conditions for 7 days and 28 days. The curing geopolymer mortar samples were carried out with compressive strength and flexural strength tests. As a result of this study, the mechanical strength of all geopolymer mortar samples containing nanomaterials increased compared to the control samples. The highest compressive strength and flexural strength were obtained from geopolymer mortar samples containing MW-CNT. These samples were followed by geopolymer mortar samples containing NS and NZ, respectively.
Keywords: Flexural strength; compressive strength; Geopolymer mortar; MW-CNT; nano-SiO2; nano-ZnO